Novo estudo isotópico de águas subterrâneas na bacia sedimentar do Cariri - Mesquita, Bruno Alves de (2013)
This work was performed in the Cariri, located in the south of the state of Ceará, where is found the largest and most important groundwater reserves of the state, the Araripe Sedimentary Basin. In this region, the main source of water for public and private supply is groundwater stored in the Cariri Valley, in the aquifers, Rio da Batateira, Missão Velha and Mauriti. Given the importance of these water reserves, several research projects have been made to obtain relevant information about the groundwater in the region. The objective of this work was to study groundwaters samples this region and to identify changes occurred during the last 16 years, using hydrochemical measures and measures of environmental isotopes oxygen-18, deuterium, carbon-13 and carbon-14. For this, we analyzed 17 samples of groundwater collected in the municipalities of Crato, Barbalha,Juazeiro, Milagres, Missão Velha and Nova Olinda. The isotope results showed that in most samples were found contributions of recent recharge, featuring young waters, with values of O-18 with minor fluctuations with respect to modern rain water and high values PMC. However, 04 samples showed a mixture of modern waters with paleowater, with low values of O-18 (<-4 permil). The apparent age of groundwater samples was calculated by the method of radiocarbon using software processing statistical data, developed in this work, and ages were corrected by the methods of Pearson, Tamers and Vogel. Regarding the results of hydrochemical parameters, bicarbonate type waters predominate for anions and the mixed type for cations: rHCO3- > rCl- > rSO4 2- e rCa2+ rMg2+ > rNa+. The waters comply with the standards of potability of CONAMA, regarding major ions, except two samples.